Review of solar energy development in Kenya: Opportunities and challenges. (June 2019) - George, Adwek; Boxiong, Shen; Arowo, Moses; Ndolo, Paul; Chepsaigutt-Chebet,; Shimmon, John
Highlights: The Kenya geographical conditions, solar energy profile and rural electrification programme discussed. Net metering coupled with smart monitoring suggested as the best option. Opportunities and constrains in the solar energy space in Kenya reviewed and the policy recommendations provided. Abstract : Kenya is still faced with a number of technical, regulatory, institutional and financial challenges in her quest to fully develop and deploy solar electrification. A critical review of these challenges is therefore necessary in order to realize the numerous benefits associated with solar energy. This review focuses on four major aspects of solar electrification in Kenya: (i) the opportunities available for solar electrification (ii) the main barriers encountered in solar electrification (iii) government policies governing solar energy and (iv) the future panorama of solar energy space. A careful analysis of all of these aspects reveals that there are enormous solar energy market opportunities in Kenya with great potential for investment, poverty eradication, and sustainable economic development that can only be realized if the government fully enforces the existing energy policies, reforms energy subsidies, provides favorable tax holidays and implements net metering mechanism in the country.